Predation of fruit and seed of Aloe pretoriensis – A little known effect on reproductive output in aloes. (2nd February 2019) - van den Bosch, Kaylee; van Noort, Simon; Cron, Glynis V.
Abstract: The effect of seed predation by phytophagous/parasitoid wasps on the reproductive output of aloes is relatively unknown. In this study, conducted at a nature reserve in Pretoria East, South Africa, the range of insects utilising Aloe pretoriensis (Asphodelaceae) fruits and/or seeds and the impact of this usage on its reproductive output were investigated. Using a GLMM, we explored the effects of morphological features (e.g. floral display size) and selected ecological factors (viz. distance between the aloes and conspecifics and other surrounding vegetation) on fruit utilisation and seed predation. A variety of insect visitors to A. pretoriensis (mainly bees and wasps) were identified including a number of seed predators and parasitoids. Evidence of phytophagy in dissected flowers showed increasing evidence of fruit utilisation and seed predation over an 8‐week period. Emergence boxes with infructescences revealed a range of insect phytophages (and their associated parasitoids) in the aloe fruits and seeds: the drosophilid fly, Apenthecia and six species of wasp – five of them associated with ultilisation of aloe fruits/seeds for the first time: Eurytoma aloineae (Chalcididae), Mesopolobus sp., Pteromalus sp., and c.f. Chlorocytus in the Pteromalidae, Bracon sp. (Braconidae) and Pediobius (Eulophidae). Fruit set ranged between 48% and 93%, with an average of 76%, while average percentage utilisation of fruits was 29%, ranging between 7% and 68%. Average seed set was 23 seeds per fruit and average percentage seed predation 21% (range: 0–51%). Fruit utilisation was found to be significantly negatively correlated with distance to the nearest flowering bush (usually Helichrysum kraussii ), but display size did not significantly affect fruit utilisation, nor did distance to conspecifics. Aloe pretoriensis thus serves as host to a variety of phytophagous insects and their associated parasitoids, which impacts considerably on its reproductive output with possible implications for the future conservation of this aloe species.